#### Answer

$a_n = (-1)^{n+1}$

#### Work Step by Step

$a_0 = (-1)^{1} = -1$
$a_1 = (-1)^{2} = 1$
$a_2= (-1)^{3} = -1$
Seeing the pattern, $a_n$ should alternate between 1, -1

Published by
Cengage Learning

ISBN 10:
0-49539-132-8

ISBN 13:
978-0-49539-132-6

$a_n = (-1)^{n+1}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.